Multicolored Memories of a Black Southern Girl - Oliver, Kitty, 1947- (Book collections on Project MUSE., 2001)
A telling memoir by an exciting new voice, Multicolored Memories of a Black Southern Girl explores journalist Kitty Oliver's coming of age as she makes the crossing from an all-black to a predominantly white world. Born and raised in an all-black area of Jacksonville, Florida, Oliver was one of the first African American freshmen to enter the University of Florida. Though she chronicles the strains of her transition from Jim Crow to desegregation, this book is much more than a memoir of the turbulent sixties. It is an upbeat journal of self-discovery in the aftermath of that decade, a look at.